ANALISIS RASIO KEUANGAN DALAM MENILAI KINERJA KEUANGAN DAERAH PEMERINTAH PROVINSI MALUKU - Tuasikal, Mundawansa; Latuamury, Jabida (Jurnal Akuntansi, 2025)
This study aims to assess the financial performance of the Provincial Government of Maluku by analyzing key financial ratios from 2019 to 2023, including regional financial independence, revenue effectiveness, budget efficiency, expenditure harmony, and fiscal growth. As a province characterized by insular geography and high dependence on central government transfers, Maluku presents unique fiscal challenges. The study employs a descriptive quantitative approach using annual data from the Regional Budget Realization Reports. The novelty of this research lies in its comprehensive evaluation of fiscal dynamics in a remote island region, contrasting with prior studies that mainly focus on mainland areas. The results indicate that the financial independence ratio consistently falls into the "very low" category, reflecting the persistent reliance on intergovernmental transfers. However, the effectiveness ratio of local revenue collection has improved significantly since 2020, indicating enhanced administrative capacity. Efficiency in budget implementation fluctuated, with fiscal deficits recorded in 2020 and 2022. Expenditure composition analysis reveals an increasing dominance of operational expenses, reaching nearly 80% in 2023, which limits fiscal space for capital investment. Despite stable capital expenditure ratios, they remain below the ideal threshold for infrastructure development. Growth indicators for both revenue and expenditure display inconsistency, raising concerns over fiscal sustainability. The study concludes that financial performance in Maluku remains constrained by structural dependence and expenditure imbalances. It recommends future research to incorporate qualitative assessments of fiscal policy implementation and explore strategies for improving regional revenue generation in archipelagic provinces.